Reducing Blocking Probability of 3G Mobile Communication System Using Time Multiplexing NOVSF Codes (International Journal of Engineering and Computer Science, 2014)
Orthogonal variable spreading factor (OVSF) codes have been proposed for the data channelization in W-CDMA access technology of IMT-2000. OVSF codes have the advantage of supporting variable bit rate services which is important for emerging multimedia with different bandwidth requirements. OVSF codes are employed as channelization codes in W-CDMA. Any two OVSF codes are orthogonal if and only if one of them is not a parent code of the other. Therefore, when an OVSF code is assigned, it blocks entire ancestor and descendant codes from assignment because they are not orthogonal to each other. This code-blocking problem of OVSF codes can cause a substantial spectrum efficiency loss. Efficient channelization code management results it high code utilization and increased system capacity.The common purpose of all of them is to minimize the blocking probability andthe reallocation codes cost so that more of new arriving call requests can be supported. The probability of code blocking due to the inappropriate resource allocation will be thus minimized using NOVSF code of spread factor 32.[1]